Evaluation of the effectiveness of one cycle of rehabilitation procedures in patients diagnosed with cervical spine discopathy - Kałużna, Anna; Pytlewska, Krystiana; Kałużny, Krystian; Dylewski, Michał; Kitschke, Ewa; Kochański, Bartosz; Hagner-Derengowska, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Aim of the study: The aim of the study was to evaluate the effectiveness of one cycle of rehabilitation procedures in patients diagnosed with cervical spine discopathy. Material and methods: The study included 100 patients (47 women and 53 men) aged 50 to 65 years (x = 57.5±4.2) with diagnosed discopathy in the lumbar spine. Patients were qualified to be examined by a physician based on the results of imaging tests and information provided in the interview. Patients were randomly divided into two groups of 50, in which two different ways of rehabilitation were applied in a 10-day ambulatory cycle. The average daily duration of therapy lasted 60 minutes. In the first group, patients underwent a series of treatments using kinesitherapy, laser therapy and magnetic field, while in the second group patients were subjected to a series of treatments using kinesitherapy, electrotherapy and TENS currents. The initial and final examination included the subjective scale of VAS pain, the ODI Oswestry questionnaire and the original scale of the assessment of the effectiveness of laser therapy, magnetic field or TENS currents. Results: Significantly less ailments were experienced by patients in a sitting position treated with laser therapy and magnetic field (M = 2.06) than with electrotherapy (M = 2.64) (p = 0.001). Less pain also caused them to travel (M = 1.78, M = 2.12) and these differences were statistically significant at p = 0.005. In patients treated with laser therapy and magnetic field, there was lower pain in a standing position (M = 2.46) than in patients treated with electrotherapy with TENS (M = 2.80) (p = 0.033). In addition, patients treated with laser therapy and magnetic field also experienced less discomfort in the conduct of social life (M = 1.86) than patients undergoing treatment with TENS (M = 2.32) (p = 0.001). Also in patients treated with laser therapy and magnetic field, significant changes in the intensity of pain were observed (M = 1.76) than in the second group (M = 2.30) - p = 0.000. In addition, patients treated with laser therapy and magnetic field showed a decrease in the level of disability (M = 20.82), while in patients treated with electrotherapy with TENS this change was lower (M = 23.22) - p = 0.000. The analysis of data on the subjective assessment of the effectiveness of rehabilitation therapy results shows that no statistically significant differences were observed due to the type of rehabilitation procedure applied. Conclusion: Kinezytherapy supported by physical procedures is an effective method of treatment of cervical spine discopathy.